Effect of an Educational Intervention on the Promotion of Dietary and Lifestyle Changes for the Prevention of Breast Cancer Among Female Teachers in Selected Schools in Selangor, Malaysia - Al-Otaibi, Hala Hazam (2008)
Breast cancer affects more women in the world today than any other cancer. Epidemiological studies have consistently shown that diet and lifestyle play a substantial role in the development of breast cancer in women. The landmark reports by the World Cancer Research Fund (1997 & 2007) concluded that cancer is largely a preventable disease. The objective of this study is to determine the effect of an educational intervention to modify the nutrition and physical activity related to breast cancer risk among female secondary school teachers in Selangor. This study aimed to improve diet and lifestyle behaviors that included fruit and vegetable intake, the total energy from fat, physical activity and anthropometric indicators. Psychosocial factors (knowledge, attitude, barriers and self-efficacy) were examined for their relationship to change in diet and physical activity. This intervention was developed based on the guidelines of the World Cancer Research Fund (WCRF, 1997; 2007) for cancer prevention, as well as the Malaysian Guidelines for Cancer Prevention of The National Cancer Society of Malaysia. A total of 210 female teachers, from eight randomly selected schools in four districts in the state of Selangor, were randomized into the intervention group (n= 108) and the control group (n= 102). The intervention group received a multi-component diet and lifestyle educational program, comprising a one-day seminar, a self-help educational module, face to face diet and lifestyle motivational counselling. The control group received only the self-help educational material after completing the final follow-up assessment. A validated and reliable questionnaire was used to obtain the necessary information, over three time points i.e: baseline, immediate (post-1) intervention and 4-months follow-up (post-2). Descriptive and multivariate analyses were used to analyze the data. The teachers were predominantly Malays, Muslims, and married with a mean age of 37 years. At baseline, the mean consumption of fruit and vegetable intakes were two servings per day in both groups, with a high proportion in both groups showing a moderate level of physical activity and body fat percentage. Both groups were at the moderate level for total knowledge and the three subscales of knowledge, attitude, barriers and self-efficacy. The results of the ANOVA - GLM Repeated Measure showed that there was a significant difference within and between the groups (p<0.05) for change in the consumption of fruit and vegetables (+0.68 serving/ day), body fat percentage (-.61%), and the multiple of resting metabolic rates (+210.56 MET), as well as for the time spent for high, moderate and walking activities, where significant changes were found within groups only. A significant difference between the groups (p<0.05) indicated an increase in knowledge, attitude, and self-efficacy, as well as a reduction in barriers in the intervention group. No significant change was observed in the control group for the consumption of fruit and vegetables, and body composition, but there was significant increase in knowledge was observed. The change in self-efficacy was found to be predictors for the change in the intake of fruit and vegetables, MET and reduction in the percentage of body fat in the intervention group. The reduction in barriers and the increase in knowledge were found to be the predictors for the reduction in the percentage of body fat. These findings suggest that the strategies used in this intervention study have had some impact in promoting positive changes in the diet and lifestyle behaviours. In conclusion, this study confirmed that apparently healthy and educated women participated in short term intervention can be motivated to increase their dietary intake of fruits and vegetables, improved their physical activity and reduce their body fat percentage.